Poly(vinyl alcohol) incorporated with surfactant based electrospun nanofibrous layer onto polypropylene mat for improved desalination by using membrane distillation - Ray, Saikat Sinha (2023)
A novel category of improved performance membrane consisting of a hydrophobic mat and a hydrophilic electrospun layer for membrane distillation (MD) application has been presented. The nanofibrous non-woven layer was fabricated by electrospinning of polyvinylalcohol (PVA) incorporated with Triton X-100 directly onto the polypropylene (PP) mat. To render the membrane distillation process effective in terms of high permeate flux and salt rejection %, the concept of dual layer membrane is utilized with hydrophobic PP mat on top and hydrophilic PVA layer on bottom. In this study, PVA nanofibrous layer has been fabricated by incorporating non-ionic surfactant Triton X-100 for uniformity and homogeneity in fiber diameter. Additionally, the PP mat acts as a top support layer and PVA-TX nanofiber acts as base layer which absorb the water molecules (condensed vapour), that enhances the vapour flux across the membrane. The modified bilayer PP/PVA-TX membranes were characterized by the pore size distribution, permeate flux, and rejection %, then compared with original PP mat. The salt rejection of the dual layered PP/PVA-TX membrane showed >99% and still maintained 2 times higher permeate flux compared to PP membrane for long term operation of 15h.